Intramedullary Nailing of Both Bone Forearm Fractures in Children by Rush Nails and Titanium Elastic Nails - Dwivedi, Rajeev; Joshi, Ruban; Byanjankar, Subin; Panthi, Sagar; Shrestha, Rahul; Ale, Som (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Forearm fractures are common upper limb injuries among children and usually treated nonoperatively. Failure of nonoperative treatment, open injuries and multiple fractures are the indications for surgery in paediatric both bone forearm fractures. Intramedullary (IM) nailing is considered as minimally invasive procedure with excellent to fair outcomes but it is not free of complications. We reviewed the results and compared the outcomes of IM fixation by Rush nails with titanium elastic nails (TENs), to understand the risks and complications associated with this procedures. MATERIAL AND METHODS: We performed a retrospective review of all paediatric patients treated for diaphyseal forearm fractures from January 2011 to December 2015. Complications were classified according to modified Clavien-Dindo complication classification system. Outcomes were graded depending upon complication grade along with range of motion of forearm. RESULTS: There was no statistically significant difference for mean time to fracture union between the Rush nailing (10.56 weeks ) group and TENs nailing group (9.85weeks) (P = 0.43). There was no statistically significant difference in outcomes between Rush nailing and TENs nailing group p=0.65. In Rush nailing group outcomes were excellent in 16 (64%), good in 7(28%), fair in 2( 8%) patients and no poor outcome were noted. In TENs nailing group outcomes were excellent in 11 (55%) , good in 6 (30%), fair in 3 (15%) patients and no poor outcomes were noted. CONCLUSION: Fixation of pediatric forearm fractures by intramedullary Rush nails and titanium elastic nails (TENs) are minimally invasive procedures and results are excellent to fair with acceptable complication rates. Since Rush nails are easily available and affordable in developing countries like ours we can prefer Rush nails for intramedullary fixation of paediatric forearm fracture when indicated. Journal of Universal College of Medical Sciences (2016) Vol.04 No.01 Issue 13, Page: 10-15